A training programme for developing motor response and balance and its effect on lunging accuracy of fencing juniors - Rawhy Abdou Abu El-Maaty, H. (World Journal of Sport Sciences, 2010)
This research aims at designing a training programme for developing motor response and balance and identifying its effect on the lunging accuracy of fencers.The researcher used the quasi-experimental approach with the experimental design of one group (pre and post- measurement). Research sample (7 fencers) was chosen in the purposefully from fencing juniors (13-15 years old) from Al-Shuban Al-Moslemeen Sports Club in Tanta for the (2009-2010 season). Then,the researcher performed review of literature in order to specify the tests related to the physical abilities under investigation and the following four tests could be achieved : motor response test and its (measured by sec), motor balance test (measured by cm), static balance test (measured by sec), lunging accuracy test (measured by sec).The periodical training method was followed in the proposed training programme and the training programme was divided into three months from 8th May to 30th July,2010 and the training load was calibrated so that the training intensity should not exceed 80% and its size three (3) weekly training units.Performance time was stated as (10-30 sec) of each exercise with (6-12) repetitions and rest intervals of (120-240 seconds) taking into consideration that pulse rate would not decline to less than (110 -120 pulse /minute).Warm-up and cool down were excluded from the training unit`s total time of 15 min. which led to an improvement of motor response and balance of its different kinds that ranged from 12.10% to 60.96% and lunging accuracy was improved by 40.86%.